Best easy day hikes Bend and Central Oregon - Dunegan, Lizann (Best easy day hikes series., 2025)
"Includes concise, easy to follow descriptions of the best short hikes in central Oregon. Gaze down at lava flows from the summit of Little Belknap Crater near Sisters, admire the colorful 400-foot-tall cliffs at Smith Rock State Park near Redmond, or enjoy stunning views of Cascade peaks on the Pilot Butte hike in downtown Bend--this book has everything you'll need to hit the trails"--